Functioning of the Copyright and Related Rights Management System - Borisova, Vladya (Research Papers, 2009)
The research observes interesting, actual and disputable matter concerning the collective management, the legal possibilities for collection of copyright remunerations, and the manner of financing the culture through authors’ remunerations deduction in a stage where the intellectual property becomes more and more significant factor for economic growth.Several points are analyzed:the existing economic situation in copyright and related rights collective management system;the structure of national collective management societies;the state participation in financing the culture development;the collective societies and state affiliation for dispensation of collected remunerations in order to support the national culture development;the obstacles in collecting the authors remunerations;the real options for increase the collection of copyright amount due;the impact of full copyright collection over the economy.The author proposes several legal recommendations for functional amelioration of the collection, deduction and dispensation of the copyright remunerations between the authors and the competent state authority in order to support the sustainable cultural development.